2010
DOI: 10.1016/j.jcin.2009.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Increased Restenosis Rate After Implantation of Drug-Eluting Stents in Patients With Elevated Serum Activity of Matrix Metalloproteinase-2 and -9

Abstract: Elevated serum activities of MMP-2 and -9 are associated with dramatically increased restenosis rates after PCI with implantation of DES. Determination of MMP levels might be useful for identification of patients who are at high risk for ISR despite implantation of DES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
4
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
0
29
4
3
Order By: Relevance
“…18 MMP-2 and MMP-9 are well known to play fundamental roles in the migration of vascular SMCs and matrix remodeling during wound healing and are produced by vascular SMCs, endothelial cells, macrophages, lymphocytes, and mast cells in response to mechanical injury. Significant elevations in MMP-9 levels at baseline and MMP-2 and MMP-9 levels 24 hours post-percutaneous coronary intervention have proven to be strongly associated with the development of ISR following DES implantation.…”
Section: Serum Matrix Metalloproteinase (Mmp) Activity and Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 MMP-2 and MMP-9 are well known to play fundamental roles in the migration of vascular SMCs and matrix remodeling during wound healing and are produced by vascular SMCs, endothelial cells, macrophages, lymphocytes, and mast cells in response to mechanical injury. Significant elevations in MMP-9 levels at baseline and MMP-2 and MMP-9 levels 24 hours post-percutaneous coronary intervention have proven to be strongly associated with the development of ISR following DES implantation.…”
Section: Serum Matrix Metalloproteinase (Mmp) Activity and Geneticsmentioning
confidence: 99%
“…Conversely low and nearnormal MMP-2 and MMP-9 levels were associated with a lack of a significant restenotic response. 18 Gene polymorphisms linked with the inflammatory response have been found to be associated with ISR. 19 As examples, homozygosity of the 16/glycine variant in the ␤ 2 -adrenergic receptor (a mediator of nitrous oxide synthetase) has been associated with ␤ 2 -adrenergic receptor downregulation and an increased risk of restenosis 19 ; Vogiatizi et al 20 described a 15-fold increase in the risk of restenosis associated with 2 functional polymorphisms of interleukin-8 (a strong mediator of inflammation).…”
Section: Serum Matrix Metalloproteinase (Mmp) Activity and Geneticsmentioning
confidence: 99%
“…A mechanical injury induces expression of matrix metalloproteinases (MMP), and there is some evidence that they may play a role in the pathogenesis of ISR (ref. [9][10][11][12] ). We found that increased levels of MMP-3 and 9 were associated with a significant increase in ISR risk.…”
Section: Matrix Metalloproteinases (Mmps) Comprise a Family Of Zinc-dmentioning
confidence: 99%
“…A mechanical damage causes expression of matrix metalloproteinases (MMP), and it is proved that they may take part in the pathogenesis of in-stent restenosis (ISR), when undergoing coronary stent implantation by percutaneous coronary intervention [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%